2009
DOI: 10.1093/jxb/erp213
|View full text |Cite
|
Sign up to set email alerts
|

Visible foliar injury and infrared imaging show that daylength affects short-term recovery after ozone stress in Trifolium subterraneum

Abstract: Tropospheric ozone is a major air pollutant affecting plants worldwide. Plants in northern regions can display more ozone injury than plants at lower latitudes despite lower ozone levels. Larger ozone influx and shorter nights have been suggested as possible causes. However, the effects of the dim light present during northern summer nights have not been investigated. Young Trifolium subterraneum plants kept in environmentally controlled growth rooms under long day (10 h bright light, 14 h dim light) or short … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…While this remains an intriguing possibility, our previous analyses suggest that the conditionality of lesion formation in cat2 is partly linked to daylength perception independent of the duration of exposure to H 2 O 2 . Consistent with this explanation, it has recently been reported that longer daylengths increase leaf injury induced by equal-time ozone exposures (Vollsnes et al, 2009). Because there is evidence for overlap between SA, pathogen responses, and the regulation of flowering (Martínez et al, 2004), the requirement for LD-dependent SA accumulation in cat2 may reflect the coordination of H 2 O 2 -triggered lesions with the flowering program.…”
Section: Peroxisomal H 2 O 2 Induces Biotic Defense Response Markers supporting
confidence: 58%
“…While this remains an intriguing possibility, our previous analyses suggest that the conditionality of lesion formation in cat2 is partly linked to daylength perception independent of the duration of exposure to H 2 O 2 . Consistent with this explanation, it has recently been reported that longer daylengths increase leaf injury induced by equal-time ozone exposures (Vollsnes et al, 2009). Because there is evidence for overlap between SA, pathogen responses, and the regulation of flowering (Martínez et al, 2004), the requirement for LD-dependent SA accumulation in cat2 may reflect the coordination of H 2 O 2 -triggered lesions with the flowering program.…”
Section: Peroxisomal H 2 O 2 Induces Biotic Defense Response Markers supporting
confidence: 58%
“…Because daylengthdependent effects have been described for redox signaling during pathogen and oxidative stress responses (Dietrich et al, 1994;Karpinski et al, 2003;Vollsnes et al, 2009), we analyzed the importance of GR1 in Col-0 and cat2 backgrounds in two growth daylengths.…”
Section: Gr1 Plays a Nonredundant Role In H 2 O 2 Metabolism And Signmentioning
confidence: 99%
“…Thermal images were obtained using a Thermovision A20 infrared camera (FLIR Systems, USA) according to VOLLSNES et al (2009). The infrared camera was mounted vertically ~10 cm above the leaf.…”
Section: Thermal Imagingmentioning
confidence: 99%